Output feedback control of flow separation over an aerofoil using plasma actuators - Broglia, R.; Choi, K.-S.; Houston, Paul; Pasquale, L.; Zanchetta, Pericle (Institute for Scientific Computing and Information, 2018)
We address the problem of controlling the unsteady flow separation over an aerofoil, using plasma actuators. Despite the complexity of the dynamics of interest, we show how the problem of controlling flow separation can be formulated as a simple set-point tracking problem, so that a simple control strategy may be used. A robust output feedback control is designed, on the basis of a low-order, linear, dynamical model approximating the incompressible Navier-Stokes equations, obtained from the snapshots of 2D laminar finite element simulations at Re=1,000. Fast flow reattachment is achieved, along with both stabilisation and increase/reduction of the lift/drag, respectively. Accurate 2D finite element simulations of the full-order nonlinear equations illustrate the effectiveness of the proposed approach: good dynamic performances are obtained, as both the Reynolds number and the angle of attack are varied. The chosen output can be experimentally measured by appropriate sensors and, despite its simplicity, the proposed set-point tracking controller is sufficient to suppress the laminar separation bubble; moreover, its extension to 3D turbulent configurations is straightforward, thus illustrating the effectiveness of the designed control algorithm in more practical conditions, which are far from the design envelope.